2010
DOI: 10.1073/pnas.1001772107
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of HLA-DP2 and implications for chronic beryllium disease

Abstract: Chronic beryllium disease (CBD) is a fibrotic lung disorder caused by beryllium (Be) exposure and is characterized by granulomatous inflammation and the accumulation of Be-responsive CD4 + T cells in the lung. Genetic susceptibility to CBD has been associated with certain alleles of the MHCII molecule HLA-DP, especially HLA-DPB1*0201 and other alleles that contain a glutamic acid residue at position 69 of the β-chain (βGlu69). The HLA-DP alleles that can present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(158 citation statements)
references
References 42 publications
7
149
0
2
Order By: Relevance
“…Genetic susceptibility to CBD is closely linked to MHCII alleles that bear a glutamic acid at position 69 of the β-chain, especially the HLA-DP2 allele (29,30). We recently solved the structure of DP2, which revealed an acidic pocket on the surface of the molecule that contained the carboxylates of β69Glu as well as two other DP2 acidic amino acids (31). Mutation of any of these amino acids eliminated Be ++ presentation to Be ++ -reactive human T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility to CBD is closely linked to MHCII alleles that bear a glutamic acid at position 69 of the β-chain, especially the HLA-DP2 allele (29,30). We recently solved the structure of DP2, which revealed an acidic pocket on the surface of the molecule that contained the carboxylates of β69Glu as well as two other DP2 acidic amino acids (31). Mutation of any of these amino acids eliminated Be ++ presentation to Be ++ -reactive human T cells.…”
Section: Discussionmentioning
confidence: 99%
“…An HLA-DP2 crystal structure revealed a unique solvent-exposed acidic pocket located between the peptide backbone and the HLA-DP2 β-chain α-helix, formed by three glutamic acid residues from the β-chain, including βGlu69 (5). Mutagenesis of any of these residues resulted in loss of the ability of HLA-DP2 to present Be to T cells (5), establishing that the HLA contribution to the development of CBD is due to the ability of βGlu69-containing HLA-DP molecules to bind and present Be to pathogenic CD4 + T cells.…”
mentioning
confidence: 99%
“…[33][34][35] Originally, this position was not considered as an anchor for DP2 binding 14 but its inclusion as an anchors QM improves the predictions. Hydrophobic amino acids, such as Trp, Tyr, and Phe, are well tolerated at position p7.…”
Section: Discussionmentioning
confidence: 99%
“…14 We assumed that for this position Coul-SR energies should be more predictive than LJ-SR energies. However, the comparative study indicated that even for this position, LJ-SR is more predictive than Coul-SR (34% vs. 26% sensitivity at the top 5% cut-off).…”
Section: Energy For Scoring the Bindingmentioning
confidence: 99%
See 1 more Smart Citation